Training to Optimize Collaborative Use of an Inpatient Portal - Hefner, Jennifer L.; Sieck, Cynthia J.; McAlearney, Ann Scheck (Applied Clinical Informatics, 2018)
Background Inpatient portals are an emerging technology that can facilitate collaborative interactions between patients and care teams, but little is known about how organizations attempt to implement and facilitate inpatient portal use for their providers.Methods We held in-person, semistructured interviews with care team members and information technology (IT) staff and conducted rigorous thematic analysis of transcripts.Results Interviews with 220 care team members and 4 IT staff identified 3 new areas of training needed to optimize inpatient portal implementation and use that extend beyond training to use other technologies: (1) teaching staff to train patients about tool use; (2) training about how to promote tool use to patients; and (3) training about optimal use of secure messaging.Discussion Our findings show that inpatient portals are implemented within a collaborative multistakeholder context. Training efforts must consider the importance of this collaborative context to help providers learn to both incorporate the technology into their workflow and assist patients with portal use.
Keywords: patient portals; hospitalization; medical informatics; implementation; training